Imaging atherosclerotic plaques by targeting Galectin-3 and activated macrophages using (89Zr)-DFO- Galectin3-F(ab')2 mAb - Varasteh, Zohreh; De Rose, Francesco; Mohanta, Sarajo; Li, Yuanfang; Zhang, Xi; Miritsch, Benedikt; Scafetta, Giorgia; Yin, Changjun; Sager, Hendrik B.; Glasl, Sarah; Gorpas, Dimitris; Habenicht, Andreas J. R.; et al. (Theranostics, 2021)
Rationale: The high expression of Galectin-3 (Gal3) in macrophages of atherosclerotic plaques suggests its participation in atherosclerosis pathogenesis, and raises the possibility to use it as a target to image disease severity in vivo. Here, we explored the feasibility of tracking atherosclerosis by targeting Gal3 expression in plaques of apolipoprotein E knockout (ApoE-KO) mice via PET imaging. Methods: Targeting of Gal3 in M0-, M1- and M2 (M2a/M2c)-polarized macrophages was assessed in vitro using a Gal3-F(ab’)2 mAb labeled with AlexaFluor®488 and 89Zr- desferrioxamine-thioureyl-phenylisothiocyanate (DFO). To visualize plaques in vivo, ApoE-KO mice were injected i.v. with 89Zr-DFO-Gal3-F(ab’)2 mAb and imaged via PET/CT 48 h post injection. Whole length aortas harvested from euthanized mice were processed for Sudan-IV staining, autoradiography, and immunostaining for Gal3, CD68 and α-SMA expression. To confirm accumulation of the tracer in plaques, ApoE-KO mice were injected i.v. with Cy5.5-Gal3-F(ab')2 mAb, euthanized 48 h post injection, followed by cryosections of the body and acquisition of fluorescent images. To explore the clinical potential of this imaging modality, immunostaining for Gal3, CD68 and α-SMA expression were carried out in human plaques. Single cell RNA sequencing (scRNA-Seq) analyses were performed to measure LGALS3 (i.e. a synonym for Gal3) gene expression in each macrophage of several subtypes present in murine or human plaques. Results: Preferential binding to M2 macrophages was observed with both AlexaFluor®488-Gal3-F(ab’)2 and 89Zr-DFO-Gal3-F(ab’)2 mAbs. Focal and specific 89Zr-DFO-Gal3-F(ab’)2 mAb uptake was detected in plaques of ApoE-KO mice by PET/CT. Autoradiography and immunohistochemical analyses of aortas confirmed the expression of Gal3 within plaques mainly in macrophages. Moreover, a specific fluorescent signal was visualized within the lesions of vascular structures burdened by plaques in mice. Gal3 expression in human plaques showed similar Gal3 expression patterns when compared to their murine counterparts. Conclusions: Our data reveal that 89Zr-DFO-Gal3-F(ab’)2 mAb PET/CT is a potentially novel tool to image atherosclerotic plaques at different stages of development, allowing knowledge-based tailored individual intervention in clinically significant disease.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Activated macrophages; Atherosclerotic plaques; Galectin-3; Inflammation; PET/CT